CULTURE SHOCK EXPERIENCED BY FOREIGN STUDENTS STUDYING AT INDONESIAN UNIVERSI-TIES - Dwi Poedjiastutie (TEFLIN Journal: A publication on the teaching and learning of English, 2009)
Abstract: This study was designed to examine the potential culture shock experienced by foreign students in Indonesian university. There were 10 foreign students who responded to the questionnaires sent by the writer through BIPA (Indonesian for foreigners) in international office of foreign studentsÃ¢â¬â¢ universities. It was found that there were three points of academic life that make foreign students experience culture shock, namely: teacherÃ¢â¬â¢s roles and attitudes; poorly organized programs; and the local studentsÃ¢â¬â¢ attitudes. In social life, it was found that foreign students experienced culture shock in 3 aspects, namely: women-men relationships; different ways of thinking and different habits.